Promoting Professional Socialization Within the Experiential Curriculum: Implementation of a High-stakes Professionalism Rubric - Tanzer, Kim (Am J Pharm Educ, 2017)
Objectives. To describe the implementation of a high-stakes rubric to assess student professionalism in introductory and advanced pharmacy practice experiences (IPPEs and APPEs) to promote the professional socialization of students in the doctor of pharmacy (PharmD) program at Western New England University (WNE). Findings. A professionalism rubric was adapted from the literature to assess the professional behavior of students enrolled in experiential courses based on evaluation of the following criteria: appropriate communication skills with patients and providers, appearance and dress code, timeliness, and initiative. The rubric was implemented in the fall semester of 2013 as a high-stakes component of the assessment within all experiential courses. Students were required to meet expectations for each of the four criteria in order to pass the practice experience, independent of their performance in other course components. Students were assessed by their preceptors at the midpoint and end of each practice experience using the appropriate evaluation tool. Each of the IPPE and APPE evaluation tools included the professionalism rubric as a requirement for assessment. Use of the Professionalism Rubric as a high-stakes assessment tool highlighted professionalism as an important component of the program, making expectations explicit to students and providing leverage to preceptors for holding students accountable. Summary. The Office of Experiential Affairs at WNE has raised awareness of the importance of professionalism and promoted the professional socialization of PharmD students with the use of a high-stakes professionalism rubric.